Padre Almeida con familia Secoyas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó al padre Almeida en compañia de un gran grupo familiar de Secoyas entre adultos niños y bebés. vestidos tradicionalmente.
ENGLISH: Father Almeida was observed in the company of a large family group of Secoyas between adults, children and babies. traditionally dressed.

SPANISH: Se observó al padre Almeida en compañia de un gran grupo familiar de Secoyas entre adultos niños y bebés. vestidos tradicionalmente.
ENGLISH: Father Almeida was observed in the company of a large family group of Secoyas between adults, children and babies. traditionally dressed.
Father Almeida with Secoyas family
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Religion|~|Evangelization|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Religion|~|Evangelización|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Religion|~|Evangelization